Placenta pathology in recipient versus donor oocyte derivation for in vitro fertilization in a setting of hypertensive disorders of pregnancy and IUGR. (May 2021) - Dancey, Sonia; Mery, Erika; Esteves, Ashley; Oltean, Irina; Hayawi, Lamia; Tang, Ken; Bainbridge, Shannon; El Demellawy, Dina
Abstract: Introduction: Assisted reproductive technology including in vitro fertilization (IVF) and oocyte donation (OD) may increase risk for placenta-mediated diseases. Comprehensive analysis of histopathological placental lesions according to source of oocytes used in the IVF procedure – recipient derived (RD-IVF) vs oocyte donation (OD-IVF), has not been conducted in a population with a hypertensive disorder of pregnancy (HDP) and/or intrauterine growth restriction (IUGR). Methods: A retrospective cohort study of archived placenta specimens from RD-IVF and OD-IVF pregnancies affected by HDP and/or IUGR was conducted with blinded histopathological placental examination. Three categories of lesions were differentiated and defined as main outcomes: maternal vascular malperfusion (MVM), chronic inflammation, and fetal vascular malperfusion (FVM). To determine the relationship between conception method and placental lesions, multivariable regressions were performed with maternal age, gestational age, HDP, birth and placental weight percentiles as model covariates. Results: 115 placentas were included 83 (72.2%) RD-IVF, 32 (27.8%) OD-IVF. Adjusted OR (aOR) for conception method was 5.05 (95%CI 0.58–43.90, p =0.142) for MVM, 1.87 (95%CI 0.68–5.15, p =0.228) for chronic inflammatory and 0.61 (95%CI 0.15–2.37, p =0.471) for FVM lesions. Multiple gestation demonstrated borderline association with MVM (aOR=0.24, 95%CI 0.04–1.51, p =0.129) and total pathology score (aRR=0.79, 95%CI 0.62–1.01, p =0.058). Subgroup analysis suggested greater odds of villitis of unknown etiology (VUE) for OD-IVF (aOR=2.98, 95%CI 1.12–7.93, p =0.029). Discussion: Source of oocyte derivation demonstrated no evidence of association with main outcomes in cases of HDP and/or IUGR. Subgroup analysis demonstrated increased rates of inflammatory lesions for OD-IVF. Multiple gestation may be associated with decreased MVM and total lesions. Highlights: Method of conception was not associated with distinct placental lesion patterns. Multiple gestation may pose a lower risk for maternal vascular malperfusion lesions. Multiple gestation may pose a lower risk for total number of placental lesions. Higher birthweight percentile may decrease number of total pathology lesions. Subanalysis shows oocyte donation may increase risk of villitis of unknown etiology.